The Effect Of Warming Up On Musculoskeletal Injuries In Cyclists - Najaah cetta Ugama; Rahajoe Imam Santosa; Raden Roro Shinta Arisanti (Jurnal EduHealth, 2023)
Musculoskeletal injury is a condition of trauma or damage that affects the function of the movement system, a complex musculoskeletal system of body tissue which is responsible for supporting movement involving the skeleton, muscles, joints, ligaments, tendons and spine. Cycling can have a risk of musculoskeletal injury if the technique and timing are not right. Most injuries to cyclists occur due to using the wrong technique and not doing enough warm-up. Cycling is very important to pay attention to warming up before doing the activity to reduce the risk of injury. There are factors that influence injury when cycling, such as not understanding the importance of warming up when exercising. Cyclists who experience injuries will cause a decline in physical function and create a feeling of trauma, resulting in decreased physical activity and poor performance. Objective: To determine the effect of warming up on the risk of musculoskeletal injuries in cyclists. Method: This research used a descriptive observational research type with a cross sectional research design approach followed by a chi square test to determine the relationship between warming up and musculoskeletal injuries. Results: Around 87.5% of cyclists who did not warm up experienced injuries, while only 13% of cyclists who did warm up experienced injuries. This shows that cyclists who warm up before cycling have a lower risk of injury. Conclusion: Musculoskeletal injuries that occur in cyclists at Taman Bungkul Surabaya are caused by a lack of warm-up and have a higher risk of injury.